Pencitraan Kematian Dalam Puisi "Out, Out" Karya Robert Frost - Ferani, Rifirin Lindya (LANTERN (Journal on English Language, Culture and Literature), 2012)
The poem entitled “Out, Out” is a poem which was written by American poet Robert Frost in the 19 th century which is set in New England. This poem tells the story of a young boy who suddenly dies after accidentally cuts his hand with a saw. The poem focuses on people's reactions to death, as well as the death itself. The aims of this thesis are to describe the intrinsic and extrinsic elements, which explain about death. The writer used two methods to compile the data; they are library research and structural approach. To get the needed data namely theories about death and moral values, the writer used library research. Meanwhile, structural approach is used by her to support the analysis in her thesis. The writer takes intrinsic and extrinsic aspects todescribe figurative language, imagery, tone, theme and explain about people’s reactions to death especially sudden death that happen to the boy in the poem. Finally, the writer concludes that Frost explains that death may occur suddenly and without warning and as a human being, we must continue our lives even in theface of tragedy.